Activities of the wintering party of the 30th Japanese Antarctic Research Expedition, 1989-1990 - Masaki Ejiri; Shigemi Meshida (National Institute of Polar Research, 1991)
The wintering party of the 30th Japanese Antarctic Research Expedition performed its activities at Syowa, Mizuho and Asuka Stations from 1989 to 1990. The wintering party at Syowa Station composed of 29 personnel carried out the routine and fundamental observations comprising aurora, geomagnetism, ionosphere, meteorology, oceanography and seismology. The multipurpose satellite data receiving system was constructed. The telemetry data of EXOS-D (aurora observation satellite) and MOS-1 (Marine Observation Satellite) have been received. This system was also successfully used for radio astronomy as a VLBI (Very Long Baseline Interferometer) to determine precise baselines among Syowa Station in Antarctica, Kashima in Japan, and Tidbinbilla in Australia. The polar patrol balloon was launched and it made a seven-eighth circumpolar orbit at a stratospheric level. As the Antarctic Climate Research programme (ACR), a meteorological PPI radar was newly operated for a continuous observation of clouds and precipitation, in addition to analyses of satellite imagery (NOAA), uninterrupted measurements of CO_2 and CH_4,radiation monitoring, etc. Unmanned and upper-air observations were carried out at Mizuho Station. Natural earthquakes were determined with several seismic sensors including STS sensors around Syowa Station. Studies were made on physiological human activities and environmental sciences. The wintering party at Asuka Station composed of 8 personnel carried out studies on the upper atmosphere physics, surface and upper-air meteorologies, ice sheet dynamics, strain to the building on the ice plateau, and physiology on human activities.